Strategi Produser Dalam Memproduksi Program Televisi Studi Kasus : Proses Produksi Program Acara Ayo Hidup Sehat Di Tvone - Defhany Defhany; Annita Zarfinal (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This research describes how the producer determining the theme of episode on the “Ayo Hidup Sehat” program, The program are aired every week. This research aims to explains the creative strategies, and obstacles that the producer faces in producing the "Ayo Hidup Sehat program" program on tvOne. This research used a qualitative method with the case study approach, by describes case study about the creative strategy of the producer to produce the television programs (Case Study: The Process of Producing the Ayo Hidup Sehat Program on tvOne). This research conducted on PT. Lativi Mediakarya tvOne which located on Kawasan Pulo Gadung, Jl.Rawaterate II No.2, Cakung, Jatinegara, East Jakarta. The informant selection used the purposive sampling technique. In this research, the informant divided into two criteria, the Key Informant is Content Producer, and the Observer Informant is Reporter. This research was conducted because of the lack of public awareness on a healthy lifestyle and the lack of a television program that contains education. So, "Ayo Hidup Sehat" program is one of the solutions to educate the public to keep a healthy lifestyle. This program discussed the health issues circulating in the public. The research found that the producer’s creative strategies are interrelated in each production process, start from pre-production, production, and post-production. The three production processes are mutually sustainable to achieve the important goal, namely rating